2020
DOI: 10.1016/j.radi.2019.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Ionising radiation exposure from medical imaging – A review of Patient's (un) awareness

Abstract: Introduction: Medical imaging is the main source of artificial radiation exposure. Evidence, however, suggests that patients are poorly informed about radiation exposure when attending diagnostic scans. This review provides an overview of published literature with a focus on nuclear medicine patients on the level of awareness of radiation exposure from diagnostic imaging. Methods: A review of available literature on awareness, knowledge and perception of ionising radiation in medical imaging was conducted. Art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
43
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 39 publications
(31 reference statements)
3
43
1
3
Order By: Relevance
“…It is their responsibility to spread awareness regarding wise use of radiation not only among other staffs in radiology department but also among the patients and the public [10]. Therefore, radiation awareness is a must to ensure rational use of ionizing radiation in medicine [13].…”
Section: Introductionmentioning
confidence: 99%
“…It is their responsibility to spread awareness regarding wise use of radiation not only among other staffs in radiology department but also among the patients and the public [10]. Therefore, radiation awareness is a must to ensure rational use of ionizing radiation in medicine [13].…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, risk communication related to the use of radiation in medical imaging has become more important and there have been several publications on the subject. [1][2][3][4] Risk communication can be defined as information about the recommended examinations, benefits and risks, and alternative imaging methods. 5 For the patients to make an informed decision this must be known to the patients, and also the risks occurring if they decided not to attend the examination.…”
Section: Introductionmentioning
confidence: 99%
“…5 For the patients to make an informed decision this must be known to the patients, and also the risks occurring if they decided not to attend the examination. 4 The patients themselves also want information concerning radiation doses and potential risks, related to their diagnostic x-ray examination. 2,4 Both referrers, radiologists, and radiographers should be able to give information about doses and risks to the patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent review conducted to identify existing literature on radiation exposure awareness of patients when undergoing nuclear medicine diagnostic scans concluded that across medical imaging there is a lack of knowledge from patients. In addition, there is a general underestimation from health professionals on ionising radiation exposure with a need for improvement in communication between professionals and patients [11].…”
Section: Introductionmentioning
confidence: 99%